All the colors of the rainbow - Fowler, Allan (New York : Scholastic, 1998)
Explains how rainbows are formed by the colors in sunlight shining through water.
K
Includes index.
590
K
Keywords: Rainbows -- Juvenile literature; Colors -- Juvenile literature; Rainbows